Comparison of Outcomes after Six Weeks Versus Two Weeks of In-Hospital Intravenous Antibiotic Therapy in Culture-Positive Infective Endocarditis: AProspective Comparative Study at Tertiary Care Setting, Multan - Rashid Minhas; Imran Javaid; Muhammad Iqbal (Life and Science, 2026)
Objective: To compare the clinical outcomes of a standard 6-week intravenous antibiotic regimen with a shortened 2-week regimen in patients with culture-positive infective endocarditis.Study Design: Prospective comparative study.Place and Duration of Study: The study was conducted at the Department of Cardiology, Chaudhry Pervaiz Elahi Institute of Cardiology (CPEIC), Multan, Pakistan, from January 2023 to January 2024.Methods: A total of 86 adult patients diagnosed with culture-positive infective endocarditis according to the modified Duke criteria were enrolled. Participants were allocated in groups in a 1:1 ratio using a computer generated sequence with allocation concealment. Allocation was stratified by baseline risk status (low vs higher risk for infective endocarditis) to ensure balanced group distribution. Owing to the nature of treatment duration, blinding of participants and treating physicians was not feasible; however, outcome assessment and data analysis were performed by investigators blinded to treatment. The first group received a 6-week course of pathogen-directed intravenous antibiotics, while the second group received a 2-week course. Baseline demographics, type of endocarditis, complications at presentation, and pathogen profiles were recorded. Patients were monitored during hospitalization and followed for six months after discharge. The primary composite outcome included all-cause mortality, relapses or persistent bacteremia, unplanned cardiac surgery, or major embolic events. Secondary outcomes included individual mortality rates, relapse, treatment success, and hospital stay. Statistical analyses were performed using SPSS version 26.0.Results: The primary composite endpoint occurred more frequently in the 2-week group (32.6%) than in the 6- week group (16.3%). In-hospital mortality (27.9% vs 14.0%) and six-month mortality (37.2% vs 20.9%) were also higher with the shorter regimen. Relapses or persistent bacteremia was more common in the 2-week group (18.6% vs 7.0%). The 2-week regimen significantly reduced hospital stay (median 20 vs 45 days).Conclusion: A 6-week regimen remains the more reliable and safer treatment strategy. How to cite this: Minhas R, Javaid I, Iqbal M. Comparison of Outcomes after Six Weeks Versus Two Weeks of In-Hospital IntravenousAntibiotic Therapy in Culture-Positive Infective Endocarditis: A Prospective Comparative Study at Tertiary Care Setting, Multan. Life andScience. 2026; 7(1): 54-60. doi: http://doi.org/10.37185/LnS.1.1.1056